2004
DOI: 10.1530/eje.0.1510375
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal stimulation of the thyroid gland with iodine or suppression during adolescence with triiodothyronine changes the prevalence of autoimmune thyroiditis in BB rats

Abstract: Objective: Changes in the functional state of beta cells by neonatal stimulation or adolescent suppression have reduced the incidence of type 1 diabetes mellitus in animal models. The aim of this study was to evaluate the effect of manipulation of the activity of the thyroid gland by neonatal stimulation or by adolescent suppression on the prevalence of spontaneous autoimmune thyroiditis (AIT) in rats. Methods: Bio-Breeding/Worcester (BB) rats were treated neonatally with sodium iodine (NaI) or thyroid stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Furthermore, a different immune response against adult compared to fetal beta cells has been shown (71). The principle of neonatal stimulation in order to diminish later autoimmunity has been extended successfully to the thyroid gland (72). It should be mentioned that to explain the lower risk of T1D in children born of diabetic mothers, compared to offspring of diabetic fathers (70), a beneficial effect of transmission of maternal islet antibodies has also been suggested (73).…”
Section: The Activity Of the Beta Cellsmentioning
confidence: 99%
“…Furthermore, a different immune response against adult compared to fetal beta cells has been shown (71). The principle of neonatal stimulation in order to diminish later autoimmunity has been extended successfully to the thyroid gland (72). It should be mentioned that to explain the lower risk of T1D in children born of diabetic mothers, compared to offspring of diabetic fathers (70), a beneficial effect of transmission of maternal islet antibodies has also been suggested (73).…”
Section: The Activity Of the Beta Cellsmentioning
confidence: 99%
“…Furthermore, a different immune response against adult compared to fetal beta cells has been shown (71). The principle of neonatal stimulation in order to diminish later autoimmunity has been extended successfully to the thyroid gland (72). It should be mentioned that to explain the lower risk of T1D in children born of diabetic mothers, compared to offspring of diabetic fathers (70), a beneficial effect of transmission of maternal islet antibodies has also been suggested (73).…”
Section: The Activity Of the Beta Cellsmentioning
confidence: 99%
“…These results reinforce the genetic influence of these autoimmune diseases. Hartoft‐Nielsen et al, however, demonstrated that sodium iodide administered neonatally by injection reduced the incidence of type 1 diabetes and insulitis 26 as well as autoimmune thyroiditis 27 in BB/Worcester rats. The reasons for this discrepancy are not apparent and might be related to factors such as differences in the timing of the treatment (neonates versus weanlings), the method of iodine treatment (injected versus oral), different rat strains, dose and duration of treatment.…”
Section: Discussionmentioning
confidence: 99%